2021
DOI: 10.3389/fphys.2021.663978
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase 3: A Promoting and Destabilizing Factor in the Pathogenesis of Disease and Cell Differentiation

Abstract: Cells must alter their expression profiles and morphological characteristics but also reshape the extracellular matrix (ECM) to fulfill their functions throughout their lifespan. Matrix metalloproteinase 3 (MMP-3) is a member of the matrix metalloproteinase (MMP) family, which can degrade multiple ECM components. MMP-3 can activate multiple pro-MMPs and thus initiates the MMP-mediated degradation reactions. In this review, we summarized the function of MMP-3 and discussed its effects on biological activities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 82 publications
0
52
0
2
Order By: Relevance
“…Among them, matrix metalloproteinases MMP-3 and MMP-13 can further promote cartilage inflammation, chondrocyte apoptosis, and ROS production, via a positive feedback loop [ 71 , 72 ]. Emerging evidence has shown that MMP13 is considered a significant biomarker to assess OA therapeutic effects and OA progression [ 73 , 74 ]. In this context, bioactive molecules able to suppress these inflammatory mediators or block the involved signaling pathway may help to reduce the OA pathological process [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among them, matrix metalloproteinases MMP-3 and MMP-13 can further promote cartilage inflammation, chondrocyte apoptosis, and ROS production, via a positive feedback loop [ 71 , 72 ]. Emerging evidence has shown that MMP13 is considered a significant biomarker to assess OA therapeutic effects and OA progression [ 73 , 74 ]. In this context, bioactive molecules able to suppress these inflammatory mediators or block the involved signaling pathway may help to reduce the OA pathological process [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, in the same condition the concentrations of other important factors for vascularization angiopoietin-1 and 2 tended to be relatively low. MMP-3, which is involved in the degradation of cartilage [42], and MMP-9, the in bone most abundant MMP also involved in endochondral ossification [43,44], tended to be relatively high in scaffolds of which defects were implanted with cartilage spheres. However, none of these concentrations differed significantly from the concentrations measured in the other conditions.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, TIMP-1 has an antagonistic function against MMP-3. Under the physiological condition, there is a balance between MMPs and TIMP-1, and any increase in TIMP-1 with or without a decrease in MMP can lead to an increase in ECM [ 68 ]. Following the P. gingivalis treatment in our study, neither MMP-3 nor TIMP-1 expression in H-GMSCs was modified, whereas MMP-3 and MMP-3/TIMP-1 ratio was significantly increased in most P-GMSC lines, all of which suggests that pathological degradation of ECM within periodontal tissues is more pronounced in the advanced stage of periodontitis.…”
Section: Discussionmentioning
confidence: 99%